"I Find It Quite a Privilege to Be Involved in Their Lives": A Multinational Qualitative Study of Program Directors' Perspectives on Their Relationships with Residents. Issue 5 (20th October 2022) - Dutta, Debalina; Stadler, Dora J.; Cofrancesco, Joseph; Archuleta, Sophia; Ibrahim, Halah
Abstract: Phenomenon: Program director ( PD)-resident relationships are important in shaping resident experiences and educational outcomes. Yet, there is limited literature on the development or meaning of these relationships, particularly from the PD perspective. Through qualitative interviews, we explore how PDs navigate their role to develop and maintain relationships with their trainees, and elucidate how these relationships impact the PDs personally and professionally. Approach: Qualitative study using individual semi-structured interviews of former and current PDs (n = 33) from multiple specialties and hospitals in accredited residency programs in Qatar, Singapore, and the United Arab Emirates. We used attachment theory and narrative analysis to investigate how PDs perceive and describe relationship building with their residents amidst tensions of familiarizing themselves with their new role. Findings: PD-resident relationships are complex and multidimensional, shifting over time, changing patterns and evolving to respond to different contexts. PDs initially negotiate their own roles, while navigating their relationships with residents and other stakeholders to create their professional identities. PDs develop professional alliances, defining for the resident the profession and its expectations. As residents negotiate the various challenges of their training, the role of the PD emerges into one of providing emotional support and advocacy. The support and attachment are often enduring and extend beyond the period of residency training. Insights: Our study examines the experiences of program directors as they negotiate complex educator-learner relationships. The PDs described roles that extended beyond their job description. Although all interviewees reported that the PD position was challenging, they focused on the rewarding aspects of the job and how their relationships helped sustain them through the difficulties. Through their reflections, the PDs described the personal satisfaction and benefits of their interactions with the residents, and how the engagement contributed to personal and professional success.